Study of Socio-Demographic Profile of Pesticidal Poisoning Cases in Tertiary Care Center - Bhandari, Binus; Saxena, Prem; Khadka, Dipendra (Journal of Nepalgunj Medical College, 2018)
Introduction: The pesticide poisoning is a common medical emergency and leads to increase morbidity and mortality rate in developing countries due to easy accessibility and low cost. The study was conducted to study the socio-demographic profile of poisoning case to understand the possible factors responsible for poisoning episodes. Method: A hospital based descriptive crosssectionalstudy was carried out in Nepalgunj Medical College, Teaching Hospital, Kohalpur, a tertiary care center, conducted for period of six months from October 2017 to March 2018. The socio-demographic profile of all cases of pesticidal poisoning attended in emergency department or admitted in medical ward were collected on a suitably designed pre- structured proforma and analyzed. Results: Total 164 patients were enrolled in the study. Majority were fallen in the age group of 20-30 years with female 76.80% dominating the male 23.20%. Married couples (74.40%) were found to be more affected and house wife was more vulnerable group 42.10%. Incidence of poisoning was more common in joint family as compare to nuclear family 81.10% versus 18.90%. Organophosphorous was most common pesticides 42.70% and suicide was main manner of poisoning. Quarrel with spouse was main reason in majority 23.80% and most of events were held at evening 69.50%. Conclusion: Pesticide poisoning was common in developing countries. More emphasis should be given on preventive measures and safety practices among the population for prevention and reduction of the pesticide poisoning.